2018
DOI: 10.5194/gmd-2018-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improvements of the hydrological processes of the Town Energy Balance Model (TEB-Veg, SURFEX v7.3) for urban modelling and impact assessment

Abstract: Abstract. Climate change and demographic pressure are common issues to be considered when conducting urban planning.Local authorities and stakeholders have therefore opted for more nature-based adaptation strategies, which are especially 10 suitable to influence both hydrological and energy processes. Assessing the multiple benefits of such strategies on the urban microclimate thus requires effective numerical tools. This paper presents recent developments of the water budget in the TEB-Veg model (SURFEX v7.3)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Efforts have been made recently to simulate the complexity of the urban environment more realistically. Urban vegetation interacting with built‐up elements, water exchanges between atmosphere, surface and soil, as well as building energetics, are new developments that have been recently implemented in urban canopy models. Such configurations now make it possible to explicitly model interactions between all these processes, to more accurately simulate specific adaptation strategies or urban design scenarios, and to enhance diagnoses.…”
Section: Analysis Methods and Impact Indicatorsmentioning
confidence: 99%
“…Efforts have been made recently to simulate the complexity of the urban environment more realistically. Urban vegetation interacting with built‐up elements, water exchanges between atmosphere, surface and soil, as well as building energetics, are new developments that have been recently implemented in urban canopy models. Such configurations now make it possible to explicitly model interactions between all these processes, to more accurately simulate specific adaptation strategies or urban design scenarios, and to enhance diagnoses.…”
Section: Analysis Methods and Impact Indicatorsmentioning
confidence: 99%
“…Using a complete vegetation and soil model to represent green roofs, De Munck et al (2018) showed that green roofs would not have a significant effect on air temperature at street level, contrary to ground vegetation and trees. Impacts on hydrology are now included in the model (Stavropulos-Laffaille et al, 2018) and will allow study of the combined UHI-hydrology impacts on Paris and its suburbs. The model developments also permitted testing of implementing alternative urban energy systems; Masson et al (2014b) showed that solar panels could be widely implemented without adverse effect on the UHI (where a slight cooling, of approximately 0.2°C, was simulated).…”
Section: Main Challenges Scientific Novelty and Innovation Of Solutimentioning
confidence: 99%